Tunable Optical Wavelength Interferometer Heterodyne System from Single Laser Source Using Fiber Bragg Grating - Kadhim, Shehab A.; Mahmood, Aseel I.; Hussien, Nahla A.; Sami, Marwa M.; Lateef, Alaa T. (International Journal of Engineering and Technology, 2018)
In this work, a new heterodyne optical system had been designed to get tunable source from single laser source using Fiber Bragg Grating (FBG), which is used as tunable element. By controlling the ambient temperature of the FBG, the wavelengths and their ranges can be controlled in way that satisfy the condition of beat frequency range. First SMF had been used in both reference arm and sensing arm. Then the system had been modified by utilizing of Photonic Crystal Fiber (PCF) in both reference arm and sensing arm. This modification provides better performance efficiency by increasing the wavelength shift of the temperature sensor. The achieved sensitivity for range from room temperature to 85 ° C was 52.01 pm/°C  for model that’s used SMF and 68.17 pm/°C  for model that’s used PCF in both reference and sensing arm. The importance of the idea is that it can be employed as a new technique in the heterodyne detection systems that have become widely applicable applications.